THE EFFECT OF FINANCE AND DIGITAL LITERATURES AND FINACIAL MANAGEMENT ON UMKM PERFORMANCE IN THE CILACAP DISTRICT - Indra Rachmawati; Nursanti Dwi Yogawati; Tri Yuwono; Fajar Nur Wibowo; Rizki Nugroho (Proceeding of The International Conference on Business and Economics, 2023)
This study aims to determine the effect of financial and digital literatures and financial management on the performance of UMKM. This research used quantitative research using associative approach. Data collection was carried out by distributing questionnaires to 30 respondents of UMKN business actors in Cilacap District. The data analysis method used is quantitative analysis using Path Coefficients Test, Modes of Goodness Test, and Hypothesis Testing. Path coefficient value of the influence of financial management on the performance of UMKM. The results of the linear test and the output of column coefficients and T-tables are known that financial management has a significant effect on performance as seen from the p value 0.005 <0.05. Good and correct financial management will provide benefits and advantages for UMKM actors. Several related institutions can provide financial and digital literatures training assistance. Training not only provides theoretical knowledge but also provides activities such as workshops and mentoring continuously.